THE INFLUENCING FACTORS ON THE GOING CONCERN AUDIT OPINION (EMPIRICAL STUDY OF MANUFACTURING COMPANIES LISTED ON THE IDX FOR THE 2017 – 2021 PERIOD) - Maria Fransisca; Temy Setiawan (SEAN Institute, 2023)
Going concern audit opinion is an opinion given when the company is in doubt about its ability to maintain its business. This research was conducted to determine the effect of firm size, audit quality, profitability, audit lag, liquidity and leverage on going concern audit opinion. This research is a qualitative study with secondary data obtained from financial statements and audit report of manufacturing companies listed on the Indonesia Stock Exchange for 2017-2021. The sample of this research is 22 manufacturing companies that was carried out using a purposive sampling method and processed with IBM SPSS version 25. The process is included descriptive analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. In this study the results have been obtained with the conclusion that firm size, profitability and leverage have no effect on goinng concern audit opinion. Meanwhile, audit quality has a negative effect on going concern audit opinion. Then for the audit lag and liquidity produce a positive effect on going concern audit opinion.